Detection and Phytoextraction of Heavy Metals by Selected Edible and Non-Edible Plants from Irrigated Sites in Kano Metropolis, Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
Heavy metal contamination in irrigated sites poses significant risks to human health and environment. The most persistent challenges are heavy metal pollution from untreated industrial effluents discharged into rivers and irrigation channels accumulates in soils and are readily transferred into crops through irrigation and root uptake. The study investigates the potential of heavy metal contamination in soils and irrigation waters across a rural-to-industrial gradient and evaluates metal uptake/partitioning in a native shrub (Dodonaea viscosa) and tomato in Kano. Laboratory analysis was carried out and CSV/Excel datasets were used to compute location-level indices (Contamination factor, Pollution Load Index, Bio concentration and Translocation factors), descriptive statistics, and between-site contrasts. Results of the findings showed the mean soil pollution load index (PLI) was highest (±8.15) at Challawa (severe multi-metal burden) and declined (±2.57) along the spatial gradient toward Dambatta and the control (±0.96). Tomato fruits from contaminated farms contained markedly elevated Lead (Pb) (2.3mg/kg) and modestly higher Cadmium (Cd) (0.6mg/kg) compared with the control (0.1mg/kg); D. viscosa preferentially retained Pb and Chromium (Cr) in roots with Pb and Cr showing low translocation (TF < 0.6), indicating retention within roots, while Zn, Cu, and Ni exhibited higher mobility (TF ≈ 0.7–0.8), and suggesting moderate phytoextraction capability Findings of the investigations had established a substantial heavy-metal pressure on wastewater-irrigated agriculture around Challawa. The shrub D. viscosa shows phytostabilization traits for Pb/Cr and moderate phytoaccumulation for Zn/Cu/Ni; however, food-crop safety is compromised, under- scoring the need for effluent control and phytoremediation.